Functional genetic evaluation of DNA house-cleaning enzymes in the malaria parasite: dUTPase and Ap4AH are essential in Plasmodium berghei but ITPase and NDH are dispensable - Kumar, Hirdesh; Kehrer, Jessica; Singer, Mirko; Reinig, Miriam; Mair, Gunnar R.; Frischknecht, Friedrich (Expert opinion on therapeutic targets, 2019)
Background: Cellular metabolism generates reactive oxygen species. The oxidation and deamination of the deoxynucleoside triphosphate (dNTP) pool results in the formation of non-canonical, toxic dNTPs that can cause mutations, genome instability, and cell death. House-cleaning or sanitation enzymes that break down and detoxify non-canonical nucleotides play major protective roles in nucleotide metabolism and constitute key drug targets for cancer and various pathogens. We hypothesized that owing to their protective roles in nucleotide metabolism, these house-cleaning enzymes are key drug targets in the malaria parasite.Methods: Using the rodent malaria parasite Plasmodium berghei we evaluate here, by gene targeting, a group of conserved proteins with a putative function in the detoxification of non-canonical nucleotides as potential antimalarial drug targets: they are inosine triphosphate pyrophosphatase (ITPase), deoxyuridine triphosphate pyrophosphatase (dUTPase) and two NuDiX hydroxylases, the diadenosine tetraphosphate (Ap4A) hydrolase and the nucleoside triphosphate hydrolase (NDH).Results: While all four proteins are expressed constitutively across the intraerythrocytic developmental cycle, neither ITPase nor NDH are required for parasite viability. dutpase and ap4ah null mutants, on the other hand, are not viable suggesting an essential function for these proteins for the malaria parasite.Conclusions: Plasmodium dUTPase and Ap4A could be drug targets in the malaria parasite.
Gesehen am 08.08.2019